2021
DOI: 10.1128/mbio.02893-21
|View full text |Cite
|
Sign up to set email alerts
|

SOS-Independent Pyocin Production in P. aeruginosa Is Induced by XerC Recombinase Deficiency

Abstract: Pseudomonas aeruginosa is a versatile and ubiquitous bacterium that frequently infects humans as an opportunistic pathogen. P. aeruginosa competes with other strains within the species by producing killing complexes termed pyocins, which are only known to be induced by cells experiencing DNA damage and the subsequent SOS response. Here, we discovered that strains lacking a recombinase enzyme called XerC strongly produce pyocins independently of the SOS response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 49 publications
(80 reference statements)
4
15
0
Order By: Relevance
“…In both P. aeruginosa and Escherichia coli , XerC acts with a second recombinase, XerD, to catalyze site-specific recombination at chromosomal dif sites to decatenate replicated chromosomes ( 13 16 ). We found that genetic inactivation of XerC recombinase activity via Phe substitution for the nucleophilic Tyr residue required for DNA cleavage and subsequent recombination ( 17 ) at the active site (XerC Y272F ) increased pyocin expression, but to a substantially lesser degree than the full xerC deletion ( 12 ). This finding suggested that loss of recombinase activity contributes to but does not fully explain the elevated pyocin expression of strains deleted for xerC .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In both P. aeruginosa and Escherichia coli , XerC acts with a second recombinase, XerD, to catalyze site-specific recombination at chromosomal dif sites to decatenate replicated chromosomes ( 13 16 ). We found that genetic inactivation of XerC recombinase activity via Phe substitution for the nucleophilic Tyr residue required for DNA cleavage and subsequent recombination ( 17 ) at the active site (XerC Y272F ) increased pyocin expression, but to a substantially lesser degree than the full xerC deletion ( 12 ). This finding suggested that loss of recombinase activity contributes to but does not fully explain the elevated pyocin expression of strains deleted for xerC .…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent lysis of pyocin-producing cells appears to be one way that fluoroquinolones kill P. aeruginosa cells, as cells mutant for recA or pyocin genes show greater resistance to such antibiotics ( 11 ). We recently discovered that strains lacking the tyrosine recombinase XerC exhibit markedly elevated basal pyocin expression that is independent of RecA ( 12 ). The overproduced pyocins released by Δ xerC strains are effective in killing sensitive strains, and xerC complementation restores wild-type levels of pyocin production ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations